PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIN KOMPENSASI, MORALITAS MANAJEMEN, KETAATAN ATURAN AKUNTANSI, DAN ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Irwansyah Irwansyah; Bambang Syufriadi (Jurnal Akuntansi, 2018)
This study aims to determine the effect of internal control effectiveness, suitability of compensation, the morality of management, the observance of accounting rules, and information asymmetry to the tendency of accounting fraud (a survey of the company's distributor in the city of Bengkulu). The data used in this research is primary data, which is obtained by spreading the questionnaire. The number of samples used in this study is 50 samples. Data analysis techniques using the help of IBM SPSS 16.0. The results showed that the effectiveness of the internal control and the morality of management negatively affect the tendency of accounting fraud. While information asymmetry has a positive effect on the tendency of accounting fraud. To the suitability of the compensation and the observance of accounting rules does not negatively affect the tendency of accounting fraud.Key words: Influence, Compensation, Management, Rules, Asymmetry, Accounting